ANALISIS KEBIJAKAN PENANGANAN MASALAH GIZI DIKALIMANTAN TIMUR BERDASARKAN PENGALAMAN BERBAGAI NEGARA - Bernatal Saragih (Pusjar SKPP Lembaga Administrasi Negara, 2010)
Over this time period, strategies for implementing effective nutrition intervention programmes have long been sought after. These have stressed not only feasibility of implementation and short-term out-comes, but efforts to promote sustainable nutrition programmes have been of great concern. The nutrition intervention programmes successed at province East Kalimantan should identified mechanisms by which experience to efforts develop recovery of community nutrition status not enough revitalization of Posyandu and Puskesmas but should be integrated development which to make a village as integrated development planning unit with nutrition as a part of welfare indicator community. To make these integrative efforts possible, political will, social mobilization, nutritionist and other related personnel must understand the nature of nutrition problems and have access to information system which provides proper and timely information. Keywords: Nutrition Problems, Intervention Programmes, Experience In Other Countries